PERBAIKAN METODE ITERASI YA NG DIPERKE NALKAN YOONMEE HAM UNTUK MENYELESAIKAN PE RSAMAAN NONLINEAR - Mis Mayra; Imran M.; Aziskhan ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
We discuss an improvement of metho d prop osed by Ham, Y. [Applied Mathematics and Computational. 222: 477–486. 2008]. Analytically we show that by adding some conditions on the weight functions, the prop osed metho d is of order five or six. Numerical comparison shows that the prop osed iterative metho ds with different weight functions do not have significant differences in terms of the number of iteration in obtaining the root.